Current and efficiency improvement for a GaAsP/SiGe on Si tandem solar cell device achieved by light trapping techniques. Issue 8 (11th July 2016) - Wang, Li; Li, Dun; Zhao, Xin; Conrad, Brianna; Diaz, Martin; Soeriyadi, Anastasia; Lochtefeld, Anthony; Gerger, Andrew; Perez‐Wurfl, Ivan; Barnett, Allen
Abstract : A GaAsP/SiGe tandem solar cell on Si substrate has been further fabricated using light trapping techniques, such as texturing and adding a back surface reflector, and thinning the Si substrate. This is of importance to increase the J sc of the Si0.18 Ge0.82 bottom cell in this tandem system since bottom cell is current limiting. The J sc of the bottom cell has been increased by relative 7.4%. This current improvement leads to a predicted efficiency of near 21% for this tandem device, with an absolute efficiency improvement of 0.3% over previous results without light trapping processes. The current of the bottom cell can be further improved by optimizing the bottom cell structure and texturing process, further thinning the Si substrate and increasing Ge concentration. (© 2016 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : A lattice‐matched and current‐matched three‐terminal GaAsP/SiGe tandem solar cell on Si substrate has been further fabricated using light trapping techniques. The J sc of the bottom cell has been increased by relative 7.4%. This current improvement leads to a predicted efficiency of near 21% for this tandem device.